Social Control Mechanisms in High Profile School: Philological Direction - Vorobiova, Antonina (Pedagogical Discourse, 2015)
The article deals with the social control mechanisms in high profile school philological direction. It is outlined that specialized general subjects are supposed to be differentiated in view of profession-oriented school (this refers to the subjects which are aimed to implement the objectives, tasks and content of each specialization in particular, and are required to be done by the students who have chosen a certain specialization) and elective courses (training courses, which are included in the content of educational program specialization, and are aimed at expanding the content of specialized subjects or providing both applied and initial professional specialization training). The ways of effective management of special school in the development phase of invariant and variant (courses to choose from) components. Variants of association as a correlative areas, and taking into account the information of the educational field (computer science). It is proved that the content of school subjects in the social sector of the philological-humanities and art- aesthetic areas can be integrated with programs minimum single rate philology.Taken into account the fact that public schools provide certain training profiles due to a combination of basic, core subjects and elective courses , providing a flexible system of school education enables school students choose an individual educational program.Given the profile orientation criteria such organization of educational institutions of different levels, in which not only realized the contents of the selected profile , but also provided the opportunity to acquire educational and important for each of them the content of the other core subjects.The essence of social communication procedures is revealed for improving the process of personal and collective communication and exchanging current information. The ways for effective management of profession-oriented school during the development of invariant and variant (courses to choose from) components are put forward. Combination options of related fields together with the informational support of educational system have been reviewed. It is proved that the content of philological subjects in social and humanities as well as art- aesthetic areas can be integrated in basic studies of philology.